Chitosan-Based Nanocarriers for Delivery of Remdesivir - Viktoria Milkova; Kamelia Kamburova; Petar Martinov; Neli Vilhelmova-Ilieva; Viktor Rashev (MDPI AG, 2023)
Stable multicomponent capsules for the delivery of remdesivir (Veklury®) are produced through subsequent electrostatic adsorption of oppositely charged components on oil emulsion droplets. For the first time, the encapsulation and release of the medicine Veklury® from polymer capsules was reported. In this study, the effect of the physicochemical properties of chitosan on the size and stability of the produced structures is investigated, on the loaded amount of drug and on the kinetics of drug release in conditions close to the physiological ones. Microbiological studies of the capsules and their constituents were performed via in vitro assays against HCT-8 cell lines and human coronavirus HCoV-OC43. A detailed analysis was performed on the influence of the properties of produced capsules on cytotoxicity against the chosen cell line, as well as their effect on the replication cycle of the virus, the virucidal activity of the samples against the viability of the extracellular virions, and their effect on viral adsorption on the cell membrane.